Key sociological thinkers (Palgrave Macmillan, 2008)
From the Publisher: This second edition of a popular and successful text offers an easily understood introduction to the theorists who have made a key contribution to the discipline of sociology. Its carefully formulated structure places the writers' passions in their social and intellectual context, summarizes the central issues dealt with in their work and sketches out the intellectual legacy they have left behind them. With four new chapters on Theodor Adorno, Michael Mann, Dorothy Smith and Zygmunt Bauman, in addition to updated references and substantial new contextual material analyzing the legacies of the theorists covered, this new edition has much to offer for students seeking to broaden their understanding of social theory.